A scoping review of intimate partner violence educational programs for health care professionals. Issue 10 (26th November 2018) - Sprague, Sheila; Swaminathan, Aparna; Slobogean, Gerard P.; Spurr, Hayley; Arseneau, Erika; Raveendran, Lucshman; Memon, Muzammil; Scott, Taryn; Agarwal, Gina; Bhandari, Mohit
ABSTRACT: Multiple intimate partner violence (IPV) educational programs have been developed for health care professionals (HCPs); however, program content and effectiveness vary substantially. The purpose of this scoping review was to identify and synthesize the literature evaluating IPV education programs for HCPs to identify key areas for potential evidence-based recommendations and focus future research priorities. We conducted a systematic literature search using broad eligibility criteria to identify studies published between January 2000 and July 2015 that evaluated the effectiveness of IPV education programs in health care settings. All potentially eligible references were screened independently by two reviewers. Data extraction was completed independently by two reviewers for all eligible studies. Descriptive statistics were used to summarize all data. We identified 65 eligible studies, 55% of which reported positive program effectiveness. Effective programs often reported the use of online training components, delivery by an IPV educator/expert or physician/surgeon, the inclusion of a treatment protocol and resources for patients and HCPs, and included more than five training sessions lasting no more than one hours each. Our results demonstrate that IPV educational programs are heterogeneous and that a wide variety of methodologies have been used to evaluate their effectiveness.